Deciding fast and slow - Daniele Pennesi (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2016)
Empirical evidence suggests that choices are affected by the amount of time available to the decision maker. Time pressure or a cooling-off period (mandatory delay of choice) changes how choices are determined. Yet, few models are able to account for the role of available time on decisions. This paper proposes a dual-self model in which a fast and a slow self bargain to decide: the longer is the decision process, the higher is the bargaining power of the slow self when deciding. A large variety of behaviors observed under time pressure or cooling-off can be explained by our model. Quantitative predictions concerning the effect of nudging through time manipulation are also provided. We characterize the model imposing testable conditions on revealed preferences combined with non-choice data.
Keywords: D01; D03; D11; D81; 330